2017
DOI: 10.5415/apallergy.2017.7.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of airborne pollen in Incheon and Seoul (2015-2016)

Abstract: BackgroundPollen allergens are one of the main contributors to the development and/or aggravation of allergic rhinitis, allergic conjunctivitis, and asthma.ObjectiveAn examination of the airborne pollen in residential areas should be conducted to aid the diagnosis and treatment of allergic diseases.MethodsAirborne pollen samples were collected from 2 sites in Incheon and 2 in Seoul from 2015 to 2016.ResultsThe highest monthly concentration of airborne pollen was observed in May and September each year. Pollen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Pinus was the most abundant genus (Fig. 2b), consistent with previous microscopy-based studies in Korea (Jung and Choi, 2013;So et al, 2017). However, DNA-based analysis showed that Pinus comprised 87% of the total plant assemblage (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pinus was the most abundant genus (Fig. 2b), consistent with previous microscopy-based studies in Korea (Jung and Choi, 2013;So et al, 2017). However, DNA-based analysis showed that Pinus comprised 87% of the total plant assemblage (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…However, DNA-based analysis showed that Pinus comprised 87% of the total plant assemblage (Fig. 2b), higher than the contributions estimated by microscopy-based analysis (42-72%) (Jung and Choi, 2013;So et al, 2017). This difference might be due to between-study variabilities in local floral and meteorological characteristics.…”
Section: Discussionmentioning
confidence: 78%
“…Seasonal variation of pollen concentrations can be altered due to climate change, landuse change and planting of street trees in the city, especially in the magnitude of pollen concentrations. [24][25][26][27] The seasonal variation indicates fluctuation in the pollen concentrations between seasons. It is, therefore, essential to update the pollen calendar using recent data.…”
Section: Introductionmentioning
confidence: 99%
“…allergic diseases in children. [12][13][14][15] Sensitization was mostly detected by skin prick tests, [12][13][14][15][16][17][18][19] while studies regarding sensitization using serum specific immunoglobulin E (serum specific IgE) tests are scarce. In a study by Yang et al, serum specific IgE in children with allergic rhinitis under the age of 18 years was detected by the MAST (multiple allergen simultaneous test), 18 but not by the ImmunoCap tests.…”
Section: Tree Pollen Sensitization and Cross-reaction Of Children Wit...mentioning
confidence: 99%